2020
DOI: 10.1093/abbs/gmaa018
|View full text |Cite
|
Sign up to set email alerts
|

circStrn3 is involved in bone cancer pain regulation in a rat model

Abstract: Bone cancer pain (BCP) is a common chronic pain that is caused by a primary or metastatic bone tumor. More detailed molecular mechanisms of BCP are warranted. In this study, we established a BCP rat model. The von Frey hair test, body weight, and hematoxylin and eosin staining were employed. We screened differentially expressed circRNAs (DECs) between the BCP group and sham group. The results revealed that 850 DECs were significantly up-regulated and 644 DECs were significantly down-regulated in the BCP group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The BCP model was established according to the method previously reported ( Zhou et al, 2015 ; Hu et al, 2019 ; Shenoy et al, 2019 ; Zhang et al, 2020 ). In detail, the young rat was intraperitoneally injected with 2 × 10 7 Walker 256 cells.…”
Section: Methodsmentioning
confidence: 99%
“…The BCP model was established according to the method previously reported ( Zhou et al, 2015 ; Hu et al, 2019 ; Shenoy et al, 2019 ; Zhang et al, 2020 ). In detail, the young rat was intraperitoneally injected with 2 × 10 7 Walker 256 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al found that circStrn3 might be a potential biomarker for bone cancer pain through regulating cancer cell apoptosis and proliferation. 17 Chen et al found that the knockdown of circStrn3 effectively inhibited cell proliferation and promoted epithelial mesenchymal transition in glomerular mesangial cells. 18 Furthermore, Thum et al con rmed that circStrn3 was regulated on doxorubicin treatment in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we successfully created BCP rat models [20]. In this study, the existence of circRNAs in the bone marrow tissues of rat BCP models was characterized by both Sanger sequencing and RT-PCR combined with agarose gel electrophoresis.…”
Section: Circular Rna Characterizationmentioning
confidence: 99%